On the equilibrium electrostatic potential and light‐induced charge redistribution in halide perovskite structures. (21st December 2021) - Regaldo, Davide; Bojar, Aleksandra; Dunfield, Sean P.; Lopez‐Varo, Pilar; Frégnaux, Mathieu; Dufoulon, Vincent; Zhang, Shan‐Ting; Alvarez, José; Berry, Joseph J.; Puel, Jean‐Baptiste; Schulz, Philip; Kleider, Jean‐Paul
Abstract: Lead halide perovskites are semiconductor materials which are employed as nonintentionally doped absorbers inserted between two selective carrier transport layers (SCTL), realizing a p‐i‐n or n‐i‐p heterojunction. In our study, we have developed and investigated a lateral device, based on methylammonium lead iodide (MAPbI3 ) in which the p‐i‐n heterojunction develops in the horizontal direction. Our research suggests that the effective doping level in the MAPbI3 film should be very low, below 10 12 cm −3 . Along the vertical direction, this doping level is not enough to screen the electric field of the buried heterojunction with the SCTL. The perovskite work function is therefore affected by the work function of the SCTL underneath. From drift‐diffusion simulations, we show that intrinsic perovskite‐SCTL structures develop mV range surface photovoltages (SPVs) under continuous illumination. However, perovskite‐SCTL structures can develop SPVs of hundreds of mV, as confirmed by our measurements. We therefore analyzed the compatibility between low doping and low defect densities in the perovskite layer and such high SPV values using numerical modeling. It is shown that these high SPV values could originate from electronic processes due to large band offsets in the buried perovskite‐SCTL heterojunctions, or at the SCTL‐transparent conductive oxide (TCO) buried heterojunction. However, such electronic processes can hardly explain the long SPV persistence after switching off the illumination. Abstract : We developed and investigated a p‐i‐n lateral device based on MAPbI3 with a 60‐μm‐long channel. Effective doping level was indirectly evaluated from XPS and drift‐diffusion models to be lower than 1012 cm −3 . KPFM measured 100 s of mV surface photovoltages (SPV) for perovskite‐transport layer (PVK‐TL) samples. The low PVK doping density cannot explain the SPV results. Partial explanation for the SPVs may be related to band offsets at the PVK‐TL or the TL‐back contact interface, or the presence of defects at the PVK‐TL interface.